PEMANFAATAN BRANDING MEDIA SOSIAL UNTUK MENINGKATKAN ATENSI DAN PENJUALAN PRODUK DI PT CP - Sudirgo, Tony; Gilbertus Brian; Lydia Suryani Tjahjadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
In the rapidly evolving digital era, a strong presence on digital platforms is essential for companies to enhance competitiveness, expand market reach, and improve brand image. PT CP, a company specializing in repackaging services for food and beverage products targeting the HOREKA sector (Hotels, Restaurants, and Cafes), has traditionally relied on conventional marketing methods that are less effective and appealing. To address this, a Community Service (PKM) activity was conducted under the theme